2008
DOI: 10.1584/jpestics.g07-29
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide sensitivities of mutated enzymes expressed from artificially generated genes of acetolactate synthase

Abstract: Mutated acetolactate synthase (ALS) genes of rice and Arabidopsis, which confer resistance to ALS-inhibiting herbicides, were generated using PCR and overlap extension. Recombinant ALSs from these mutated genes were prepared as glutathione S-transferase-fused proteins, and sensitivities of the proteins to ALS-inhibiting herbicides were examined. Nine kinds of rice ALSs that have mutations at the P171 position (each amino acid is represented by one letter) showed high resistance to a herbicide, bensulfuron-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 14 publications
2
24
0
Order By: Relevance
“…The ALS activity of W574L/ S653I plants was strongly resistant to PS, BM and IP (Figure 8). The selectable tolerance of plants transplastomic with G121A, A122V and W574L/ S653I ( Figure 9) were similar to those obtained when using the same recombinant mALSs that only expressed the catalytic subunit in E. coli, to which endogenous E. coli regulatory subunits, it was concluded, were not associated (Tables 1 and 2) (Kawai et al, 2008;Okuzaki et al, 2007). Therefore, the regulatory subunits do not affect the sensitivity of these mALSs to herbicides in transplastomic plants.…”
supporting
confidence: 69%
See 4 more Smart Citations
“…The ALS activity of W574L/ S653I plants was strongly resistant to PS, BM and IP (Figure 8). The selectable tolerance of plants transplastomic with G121A, A122V and W574L/ S653I ( Figure 9) were similar to those obtained when using the same recombinant mALSs that only expressed the catalytic subunit in E. coli, to which endogenous E. coli regulatory subunits, it was concluded, were not associated (Tables 1 and 2) (Kawai et al, 2008;Okuzaki et al, 2007). Therefore, the regulatory subunits do not affect the sensitivity of these mALSs to herbicides in transplastomic plants.…”
supporting
confidence: 69%
“…Recombinant Arabidopsis mALSs, AtALS-W574L/ S653I and -S653I, were expressed in Escherichia coli cells. These recombinant mALSs exhibited resistance to PCs, and showed similar sensitivity against herbicides to rice recombinant ALSs with the corresponding mutations (Table 1) (Kawai et al, 2008). We have shown that these Arabidopsis ALS genes can also be utilized as selectable markers for the genetic transformation of Arabidopsis (Kawai et al, 2010).…”
Section: Als Mutations Interfering With Herbicide Actionsmentioning
confidence: 80%
See 3 more Smart Citations